Effect of Human Capital development on the Financial Performance of Banks in Nigeria: A Study of Selected Public Quoted Commercial Banks (2005-2015) - Ezeagba, Charles Emenike (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
The main objective of this study is to determine effect of human capital development on the financial performance of banks in Nigeria. The specific objectives were to find out if there exist a significant relationship between human capital development and earnings per share , net profit margin, return on asset and return on equity of banks in Nigeria. To achieve the aim of this study, the Ex-post facto research design and secondary data were used. Data on EPS, PAT, Personnel cost, Total asset, Equity and were extracted from 2005-2015 annual financial statement of selected quoted commercial banks. Data on human capital (HCROI was the proxy used for measuring human capital) which was the independent variable, and financial performance indicators (EPS, NPM, ROA, ROE) which were the dependent variables were subjected to simple regression technique in order to analyze and establish the relationship between the variable and to test the hypotheses. The test showed that there no significant relationship between human capital development and EPS of banks in Nigeria, since p= sig= 0.350 > 0.05. However human capital was seen to have a strong positive relationship with net profit margin, return on asset , and return on equity which was 0.904, 0 .866 and 0.340 respectively as indicated by the R, which was the correlation coefficient of the two variables , also R2 which were 0.818, 0.750 and 0.115 , further revealed that human capital development accounts for 81.8%, 75% and 11.5% , contribution in Net Profit Margin , Return on asset and Return on equity of banks in Nigeria respectively, also their test showed that there was a significant relationship between human capital development and these variables since p= sig= .000 0.05 . The study shows that the importance of human resource development cannot be overemphasized in the banking industry, and that proper and adequate investments in human capital development in the banking sector will indeed bring about positive improvement in their organizational performance . Based on the findings, it was recommended that efforts should be intensified by the banking institution and the government to increase investment on Human capital, which in the long run will lead to an increase in the performance of these institution and the country at large.